Multi-Analytical Research on the Caisson Painting of Dayu Temple in Hancheng, Shaanxi, China - Jiaxin Li (MDPI AG, 2021)
In this research, the caisson painting of Dayu Temple in Hancheng, Shaanxi, China, was analyzed via a multi-analytical methodology, using a pH meter, an ultra-depth-of-field optical microscope, a scanning electron microscope-energy dispersive spectrometer (SEM-EDS), a high-resolution X-ray diffractometer (XRD), a micro-confocal laser Raman spectrometer, a gas chromatography mass spectrometer (GC-MS), and X-ray fluorescence spectroscopy (XRF). With the corroborative evidence derived from the above analyses, it could be determined that the caisson painting of Dayu Temple was painted on bamboo paper and attached to hemlock wood substrate of the Pinaceae Tsuga genus using starch paste, with common colorants such as carbon black, cinnabar mixed with a small amount of red lead, ultramarine, and ultramarine mixed with Paris green, with animal glue having been adopted as a sizing agent. These results provide important scientific data for the production craft of precious caisson paintings, contributing to the revelation of their historic, artistic, and scientific value, and should enable conservators to make informed decisions in restoration.